Faktor-Faktor Yang Mempengaruhi Literasi Keuangan Mahasiswa Pendidikan Akuntansi di Era Digital - Dudung Ma'ruf Nuris; Tsania Rahmawati (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2021)
Attention of various countries to financial literacy is increasing in line with the more complex economic sector growth, with rapid development of financial technology and variety of new financial products and services offered. College students as the next generation are expected to have good financial literacy in order to be able to overcome the increasingly complex economic problems. This study aims to test the influence of socioeconomic factors (pocket money, parent’s latest education, and parent’s income) to financial literacy. This study used a quantitative approach with an explanatory research design and survey method. The data collecting were taken by tests and questionnaires conducted on a sample of 215 undergraduate students of Accounting Education, State University of Malang, with the sampling technique used simple random sampling. The data collected were then analyzed by multiple linear regression. The results of the data analysis show that: pocket money has a positive and significant effect on student’s financial literacy, parental education has no positive and significant effect on student’s financial literacy, and parents’ income has no positive and significant effect on student’s financial literacy. Based on the data analysis above, it can be concluded that this result are not enough to support the socioeconomic theory, that socioeconomic status can affect person’s knowledge, behavior, and attitudes, in this case student financial literacy.